Design and Development of the Space Shooters Game Using Pygame - Jazuli, Muhammad Syauqi; Rizki, Muhammad (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
Space Shooter is a game that aims to shoot all the asteroids emerging from space while keeping the spaceship from colliding with them by maneuvering the spaceship. The main objective of this game is to accumulate as many points as possible by accurately shooting the asteroids. This game is developed using Pygame, a cross-platform Python module library designed for writing video games. Pygame includes computer graphics and sound libraries designed for use with the Python programming language. This study explores the development process of the